2021
DOI: 10.1525/elementa.2021.00037
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungal response to fire and urbanization in the Great Smoky Mountains National Park

Abstract: Wildfires are increasing in frequency and intensity as drier and warmer climates increase plant detrital fuel loads. At the same time, increases in urbanization position 9% of fire-prone land within the United States at the wildland–urban interface. While rarely studied, the compounded effects of urbanization and wildfires may have unknown synergistically negative effects on ecosystems. Previous studies at the wildland–urban interface often focus on aboveground plant communities, but belowground ecosystems may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Although Pressler et al . (2019) described a decrease in fungal biomass after fires in grasslands, whether prescribed fires or wildfires, in cases where the plant community composition remains largely intact, the AMF flora may easily recover after prescribed burns (Kivlin et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Pressler et al . (2019) described a decrease in fungal biomass after fires in grasslands, whether prescribed fires or wildfires, in cases where the plant community composition remains largely intact, the AMF flora may easily recover after prescribed burns (Kivlin et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Prescribed burns during the dormant season have little effect on hemicryptophytes and geophytes on account of the low heat conductivity of the soil and rapid combustion of plant residues. Although Pressler et al (2019) described a decrease in fungal biomass after fires in grasslands, whether prescribed fires or wildfires, in cases where the plant community composition remains largely intact, the AMF flora may easily recover after prescribed burns (Kivlin et al, 2021).…”
Section: Amf Diversity and Communitymentioning
confidence: 99%
“…Conversely, Kivlin et al (2021), investigated the response of mycorrhizal fungi to urbanization and fire in the United States and while they found that urbanization and fire affected some fungal metrics independently, no interaction between urbanization and fire was identified. However, neither of these studies involved vertebrate species and all sampling sites were within either National or State parks surrounded by urban zones.…”
Section: Discussionmentioning
confidence: 99%
“…Beal‐Neves et al ( 2020 ), using time since fire as a variable, examined fire disturbance and urbanization on pollinating faunas, specifically insects, in South Brazilian grasslands and found that fire disturbance events became more frequent with an increase in urbanization; further, they found that the richness of floral visitors was positively correlated with an increase in urbanization. Conversely, Kivlin et al ( 2021 ), investigated the response of mycorrhizal fungi to urbanization and fire in the United States and while they found that urbanization and fire affected some fungal metrics independently, no interaction between urbanization and fire was identified. However, neither of these studies involved vertebrate species and all sampling sites were within either National or State parks surrounded by urban zones.…”
Section: Discussionmentioning
confidence: 99%